2006
DOI: 10.1080/13693780500417037
|View full text |Cite
|
Sign up to set email alerts
|

Honey has an antifungal effect againstCandidaspecies

Abstract: The incidence of Candida infections is escalating worldwide. The serious nature of these infections is compounded by increasing levels of drug resistance. We report that certain honeys have significant antifungal activity against clinical isolates of Candida species. Importantly, the minimum inhibitory concentration of these honeys would be achievable in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(110 citation statements)
references
References 24 publications
4
103
0
3
Order By: Relevance
“…In the same way, previous reports demonstrated that increased honey concentrations resulted in reduced growth of C. albicans, namely 29.4% inhibition on the growth was verified in the presence of wasbessie honey at concentrations of 25% (Theunissen et al 2001). The minimum inhibitory concentration of honeys against isolates of Candida species (C. albicans C. glabrata and C. dubliniensis) would be achievable in a clinical setting (Irish et al 2006); C. dublinensis was more susceptible to the osmotic effect of all honeys, and to the antifungal effects of Jarrah honey. However, on the other hand, previous studies with different types of honey tested at several concentrations ranging from 0.1 to 20% (Lusby et al 2005) and from 25 to 100% (Omafuvbe and Akanbi 2009) revealed that the growth of C. albicans was not inhibited by the honeys.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the same way, previous reports demonstrated that increased honey concentrations resulted in reduced growth of C. albicans, namely 29.4% inhibition on the growth was verified in the presence of wasbessie honey at concentrations of 25% (Theunissen et al 2001). The minimum inhibitory concentration of honeys against isolates of Candida species (C. albicans C. glabrata and C. dubliniensis) would be achievable in a clinical setting (Irish et al 2006); C. dublinensis was more susceptible to the osmotic effect of all honeys, and to the antifungal effects of Jarrah honey. However, on the other hand, previous studies with different types of honey tested at several concentrations ranging from 0.1 to 20% (Lusby et al 2005) and from 25 to 100% (Omafuvbe and Akanbi 2009) revealed that the growth of C. albicans was not inhibited by the honeys.…”
Section: Introductionsupporting
confidence: 60%
“…To date, very few attempts have been made to assess the antifungical properties of honey (Theunissen et al 2001;Irish et al 2006;Küçük et al 2007;Boukraa et al 2008;Koc et al 2008), especially as compared to the large volume of published literature which has established that honey has significant antibacterial activity. The incidence of fungal infections is increasing in community and hospital environments (Fridkin 2005) and no other mycotic patho-gen produces as great a spectrum of opportunistic diseases in humans and animals as Candida does (Pappas et al 2003;Tortorano et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nowadays many researches are focused on the therapeutical properties of natural compounds [31] . Honey is a natural product that is used for its antifungal activity [14] . Several factors may influence the antifungal activity of honey.…”
Section: Discussionmentioning
confidence: 99%
“…as fungal strains. Results: The range of the diameter of zone of inhibition of various concentrations of tested honeys was (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) mm) for Rhodotorula sp., while C. albicans showed clearly resistance towards all concentrations used. The MICs of tested honey concentrations against C. albicans and Rhodotorula sp.…”
Section: Honey Samplesmentioning
confidence: 99%
See 1 more Smart Citation